Psychometric properties of the Epistemological Development in Teaching Learning Questionnaire (EDTLQ): An inventory to measure higher order epistemological development - Sofia Kjellström; Hudson Golino; Rebecca Hamer; Erik Jan van Rossum; Ellen Almers (EARLI, 2016)
Qualitative research supports a developmental dimension in views on teaching and learning, but there are currently no quantitative tools to measure the full range of this development. To address this we developed the Epistemological Development in Teaching and Learning Questionnaire (EDTLQ). In the current study the psychometric properties of the EDTLQ were examined using a sample (N= 232) of teachers from a Swedish University. A confirmatory factor and Rasch analysis showed that the items of the EDTLQ form a unidimensional scale, implying a single latent variable (eg epistemological development). Item and person separation reliability, showed satisfactory levels of fit indicating that the response alternatives differentiate appropriately. Endorsement of the statements reflected the preferred constructivist learning-teaching environment of the response group. The EDTLQ is innovative since is the first quantitative survey to measure epistemological development and it has a potential to be used as an apt tool for teachers to monitor the development of students as well as to offer professional development opportunities to the teachers.